PENGELOLAAN LAYANAN PENGEMBANGAN DIRI SISWA DI SMP NEGERI 2 TOROH KECAMATAN TOROH KABUPATEN GROBOGAN - SUNTORO , SUNTORO (2011)
Research purposes are: (1) describing self development activity planning in 2 Toroh Government Junior High School Toroh Subdistrict Grobogan District. (2) describing student self development activity execution in extracurricular in 2 Toroh Government Junior High School Toroh Subdistrict Grobogan District. (3) describing self development activity evaluation in 2 Toroh Government Junior High School Toroh Subdistrict Grobogan District.